Pengaruh Inflasi, BI Rate, CAR, NPL, BOPO Terhadap ROA pada Bank HIMBARA (Himpunan Bank Milik Negara) yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2023 - Putri, Wida Amelia; Tristanto, Triyono Adi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The focus of this study is to examine and evaluate the Return on Asset (ROA) which is influenced by Inflation, BI Rate, Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Income Operating Expense (BOPO) on Bank HIMBRA (Association of State-Owned Banks) listed on the Indonesia Stock Exchange during 2019 to 2023. The approach used in the study is Quantitative Descriptive by utilizing secondary data, the methodology used is a saturated sample technique. The test results showed that there were two (2) independent variables that had a partial significant influence on ROA, namely with a Sig. value of 0.001 lower than 0.05, while for the other three (3) variables did not show a significant influence on ROA, namely the Inflation variable had a Sig. value of 0.807>0.05, the BI Rate variable had a Sig. value of 0.704>0.05, and the NPL variable has a Sig. value of 0.109>0.05. However, based on the results of the Hypothesis Test, a value of Sig. 0.000<0.05 was obtained, so it can be concluded that the independent variables simultaneously have a significant influence on ROA.